حركة التأليف فى بلاد شنقيط: مؤلفات الولاتيين أنموذجا - ابن السبتي، إسلم (مركز جمعة الماجد للثقافة والتراث - قسم الدراسات والنشر والشؤون الخارجية, 2017)
This research aspires to record the intellectual production of Wolati scholars that covers the most of the sciences known in our time. This work was done in the following entries; Quran and its sciences, exegesis, doctrine, monotheism, biography, eulogy, Hadith, mysticism, secret sciences, jurisprudence, calamity, tips, rhetoric, grammar, letters, answers and replies, Animal life, prosody, poetry, journey art, astronomy and arithmetic. At each entrance, we dealt with most of the works we came across, which required at least one paragraph for each entry, the entry may be divided into paragraphs that may sometimes reach to fourteen, as is the case with the entry of Fiqh.
Keywords: الإنتاج الفكري -- التراث الثقافي -- المصادر التاريخية -- موريتانيا